2016
DOI: 10.1016/j.amjcard.2015.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Torsemide Versus Furosemide in Patients With Acute Heart Failure (from the ASCEND-HF Trial)

Abstract: Furosemide is the most commonly used loop diuretic in heart failure (HF) patients despite data suggesting potential pharmacologic and anti-fibrotic benefits with torsemide. We investigated HF patients in ASCEND-HF who were discharged on either torsemide or furosemide. Using inverse probability weighting to account for the non-random selection of diuretic, we assessed the relation between choice of diuretic at discharge with 30-day mortality or HF hospitalization and 180-day mortality. Of 7,141 patients in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 29 publications
3
35
1
Order By: Relevance
“…In recent years, two retrospective studies with large sample sizes suggested that torsemide was associated with similar outcomes compared with furosemide. 12,13) We did not observe significantly improved outcomes with torsemide use in our HF cohort, the specific reason for which remains unclear. Compared with previous studies 6,7) that were conducted decades ago, our study cohort had higher usage rates for ACEI/ARB, beta blockers, and spirolactone, which could inhibit the renin-angiotensin-aldosterone system (RAAS) and sympathetic nervous system.…”
Section: 7)mentioning
confidence: 73%
See 3 more Smart Citations
“…In recent years, two retrospective studies with large sample sizes suggested that torsemide was associated with similar outcomes compared with furosemide. 12,13) We did not observe significantly improved outcomes with torsemide use in our HF cohort, the specific reason for which remains unclear. Compared with previous studies 6,7) that were conducted decades ago, our study cohort had higher usage rates for ACEI/ARB, beta blockers, and spirolactone, which could inhibit the renin-angiotensin-aldosterone system (RAAS) and sympathetic nervous system.…”
Section: 7)mentioning
confidence: 73%
“…Importantly, while the associations between decreased mortality and torsemide in two retrospective studies and our study were not statistically significant, after adjustment the value of point estimation continued to trend towards a better outcome with torsemide in these 3 studies. 12,13) In our logistic analysis, we found that a higher NYHA classification and higher UA were associated with combination treatment. There are several potential reasons for the preference of combination treatment.…”
Section: 7)mentioning
confidence: 83%
See 2 more Smart Citations
“…Post‐hoc analyses of trials conducted on patients admitted with acute heart failure and discharged on either furosemide or torasemide have also been performed. As an example the ASCEND‐HF trial examined the effects of nesiritide in heart failure . A recent post‐hoc analysis examined patients discharged on either torasemide or furosemide and suggested a tendency for a reduction in mortality in torasemide‐treated patients, but this did not reach statistical significance.…”
Section: Trials Of Safety and Efficacymentioning
confidence: 99%